Mixed convective peristaltic flow of carbon nanotubes submerged in water using different thermal conductivity models. Issue 135 (October 2016) - Hayat, T.; Ahmed, Bilal; Abbasi, F.M.; Ahmad, B.
Highlights: Peristaltic transport of CNTs-water nanofluid through an asymmetric channel is examined. Velocity slip, temperature jump, heat generation/absorption and mixed convection effects are taken into account. Mathematical modeling is carried out using the long wavelength and low Reynolds number approximations. Series solutions for the axial velocity, pressure gradient, temperature and heat transfer rate at the wall are obtained. Comparison between thermal conductivity models is also presented for future reference. Abstract: Background and Objective: Single Walled Carbon Nanotubes (SWCNTs) are the advanced product of nanotechnology having notable mechanical and physical properties. Peristalsis of SWCNTs suspended in water through an asymmetric channel is examined. Such mechanism is studied in the presence of viscous dissipation, velocity slip, mixed convection, temperature jump and heat generation/absorption. Methods: Mathematical modeling is carried out under the low Reynolds number and long wavelength approximation. Resulting nonlinear system is solved using the perturbation technique for small Brinkman's number. Physical analysis and comparison of the results in light of three different thermal conductivity models is also provided. Conclusions: It is reported that the heat transfer rate at the boundary increases with an increase in the nanotubes volume fraction. The addition of nanotubes affects the pressure gradient during the peristaltic flow. Moreover, the maximum velocity of the fluid decreases due to addition of the nanotubes.